2022
DOI: 10.1149/1945-7111/ac8646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Laser on Abnormal Reduction Process and Properties Evaluation of Electrodeposited Soft Magnetic Fe-Ni Coating

Abstract: Electrodeposition process of Fe-Ni coating belongs to abnormal co-deposition according to Brenner’s classification, in which Ni is mainly affected by activation, and Fe is mainly affected by diffusion. In this paper, Fe-Ni coating was prepared by laser-assisted electrodeposition technology. The regulation of Fe and Ni contents and coating properties is achieved by using the influence of laser thermal and force effects on the abnormal co-deposition process. The results show that the laser positively shifts the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…It is noted that resolution can be easily controlled, and a wide range of structural dimensions can be achieved by varying the laser power and fixing the spot size. The introduction of lasers in the field of electrodeposition reduces the energy barrier of metal ion reduction. Von Gutfeld et al found that laser irradiation during electrodeposition can significantly increase the current density in the irradiated region, and the maskless preparation of metal patterns was successfully achieved by laser scanning. Gupta et al used a green laser for unmasked copper plating on stainless steel surfaces, noting that the thickness of the plated layer depends on the time of plating and the incident laser power density, while excessive laser power brings about the removal of the material and lateral thermal diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that resolution can be easily controlled, and a wide range of structural dimensions can be achieved by varying the laser power and fixing the spot size. The introduction of lasers in the field of electrodeposition reduces the energy barrier of metal ion reduction. Von Gutfeld et al found that laser irradiation during electrodeposition can significantly increase the current density in the irradiated region, and the maskless preparation of metal patterns was successfully achieved by laser scanning. Gupta et al used a green laser for unmasked copper plating on stainless steel surfaces, noting that the thickness of the plated layer depends on the time of plating and the incident laser power density, while excessive laser power brings about the removal of the material and lateral thermal diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-Ni alloys, which are widely utilized in industries including aerospace, electronics, and information technology, are excellent magnetic materials with high saturation magnetization, low coercivity, and superior corrosion resistance. [1][2][3] Traditionally, Fe-Ni alloy films are prepared by the rolling method, but also by rapid solidification, sputtering deposition, electrodeposition, and ball milling. [4][5][6] Electrodeposition has several advantages over other methods, such as precisely regulating the shape and thickness of the product, while the preparation process is simple and economically feasible.…”
mentioning
confidence: 99%